Representasi Calon Arang Sebagai Simbol Teknologi Dalam Iklan Marjan 2025 - Suardi, Melisa; Apriliana (Jurnal Sains Informatika Terapan, 2025)
This research examines the transformation of Calon Arang mythology in the Marjan 2025 advertisement, which represents the character as an artificial intelligence (AI) in the futuristic world of JKTerra in 2108. Using Roland Barthes' semiotic approach, the analysis focused on the denotative, connotative, and mythical meanings contained in the visual representation of the ad. The results show that this advertisement successfully combines traditional and modern elements, and conveys social criticism of the dominance of technology in human life. Calon Arang's transformation into an AI reflects contemporary concerns about the rapid development of technology, as well as the importance of maintaining a balance between technological progress and human values. This research contributes to understanding branding strategies that combine local culture and global issues in the Indonesian advertising industry.